PEMASARAN SAGU TUMANG DI DISTRIK INANWATAN KABUPATEN SORONG SELATAN - Hendry Jems Yoel Aidore; Krisna Fransina Lermating; Franklin Donaldson Paiki (P3M Politeknik Negeri Ambon, 2022)
This research aims to determine the marketing channels for Tumang sago and the price level, costs and income of Tumang sago entrepreneurs in Inanwatan District, South Sorong Regency. Each sample village involved 5 Tumang sago entrepreneurs. Tumang sago entrepreneurs in the Inanwatan District with case studies totaling 45 Tumang sago entrepreneurs. Primary data was collected by direct interviews with respondents using the Focus Group Discussion (FGD) method using a questionnaire (list of questions). There is one marketing channel for Tumang sago at the research location, namely marketing channel I: producer to final consumer. The price of small and large sago tumang ranges from IDR 100,000 to IDR. 350,000 with the highest average monthly gross income in Serkos Village Rp. 4,710,000/org, followed by Mate Village Rp. 2,560,000/org, Mogibi Village Rp. 2,400,000 and also Siri-siri Village Rp. 2,000,000 and Sibae and Odeari villages had the same gross income of Rp. 1,810,000, while Wadoi Village received a gross income of Rp. 1,590,000, followed by Isogo Village, Rp. 1,300,000 and the lowest gross income was in New Solta Village, Rp. 1,040,000. The costs incurred by Tumang sago entrepreneurs in the Inanwatan District are based on villages, namely Wadoi Village with an average total cost of IDR 456,292.66/org, Serkos Village with an average total cost of IDR 334,426.22/org, Odeari Village with average total cost IDR 286,959.66/org, Solta Baru Village with average total cost IDR 255,051.03/org, Mate Village with average total cost IDR 249,057.59/org, Mogibi Village with total average cost IDR 244,046.96/org, Siri-siri Village with an average total cost IDR 183,735.55/org, Sibae Village with an average total cost IDR 170,570.11/org and Isogo Village with an average total cost -average IDR 151,165.35/person. The income of Tumang sago entrepreneurs in Inanwatan District is classified as very high compared to the Papua Minimum Wage, so the highest income for Tumang sago entrepreneurs from Serkos Village is siri amounting to Rp. 2,216,264.45/org, Mogibi village income amounting to Rp. 2,155,953.04/org, Odeari Village income amounting to Rp. 1,523,040.34/org, Sibae Village income amounting to Rp. 1,259,429.89/org, Isogo Village amounting to IDR 1,148,834.65, Wadoi Village is IDR 1,133,707.34 and the lowest average income is in Solta Baru Village IDR 784,948.97 /org. Keywords: Tumang Sago, Price, Costs and Income